Higher-order sliding mode observer and fractional-order sliding mode control for precise wildfire tracking in heterogeneous multi-agent systems - Ammar Alsinai; Aasma Zaman; Azmat Ullah Khan Niazi (Systems Science & Control Engineering)
This study considers the complications caused by collaborative wildfire tracking in unmanned air vehicles and unmanned ground vehicle heterogeneous multi-agent systems with various types of faults like actuator and sensor faults throughout fire tracking. A control technique for formation control using fractional-order non-singular fast terminal sliding mode (FO-NFTSM) control approach to entitle the heterogeneous multi-agent system to track wildfire dispersion. Moreover, a higher-order sliding mode observer (HOSMO) is mapped out to evaluate velocities and multi-source instabilities that come about from external perturbation, system uncertainties, and sensor and actuator faults. HOSMO and FO-NFTSM techniques lead us to the validity of initiate techniques for precise wildfire tracking.